Corruption intensify poverty - Imad Ibrahim Ali Al-Sultan; Jasni Sabri (2015)
The relationship between poverty and corruption is well understood in many recent studies. This interaction can be a good tool and index to develop programmes in poverty reduction strategies. Corruption in the public sector is often viewed as exacerbating conditions of poverty. Scientist agrees that corruption directly does not produce poverty but it has direct implications on the economy and governance polices lead to poverty. Accordingly all reports and investigations in that respect are indirect. The Economic Model assumes that corruption limiting economic growth. On the other hand the absence of economic growth increases poverty. Inversely, tests have shown that an increase in Gross domestic product produces an increase in the income of the poor. However, income distribution is an important mediating factor because economic growth may not always benefit the poor. Corruption affects poverty by influencing governance factors, which, in turn, impact poverty levels. Corruption reduces governance capacity, and weakens political institutions and citizen participation and leads to lower quality government services and infrastructure. The poor suffer disproportionately from reduced public services. When health and basic education expenditures are given lower priority the illiteracy dominates the society and eventually reduces public trust in government institutions. This paper focuses on the linkage between corruption and poverty and demonstrates that corruption does exacerbate and promote poverty.